Linguistic Categories and Expression in Javanese Language of The Coastal Community In Banjar Kemuning Village, Sidoarjo (Komunitas, 2019)
Â This study reveals all Javanese language categories and expressions of the coastal community of Banjar Kemuning village, Sidoarjo district through the perspective of ethnolinguistic studies. This type of research is descriptive qualitative. This research uses ethnographic methods with the analysis model that is the ethnoscience model. The results of this study indicate that through the mindset and knowledge system of society, it has been found all kinds of Javanese language categories and expressions in their speech expressions in the form of a way of life in terms of livelihoods as fishermen and pond farmers, the names of fishing tools and pond farmers, the names of sea products, a set of terms of offerings and various rituals, mantra or prayers as well as local wisdom of the village community hidden behind verbal and non verbal expressionsÂ Â